Digital Signal Processing for Wireless Communication using Matlab - Gopi, E.S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book examines signal processing techniques used in wireless communication illustrated by using the Matlab program. The author discusses these techniques as they relate to Doppler spread; delay spread; Rayleigh and Rician channel modeling; rake receiver; diversity techniques; MIMO and OFDM -based transmission techniques; and array signal processing. Related topics such as detection theory, link budget, multiple access techniques, and spread spectrum are also covered.   ·         Illustrates signal processing techniques involved in wireless communication using Matlab ·         Discusses multiple access techniques such as Frequency division multiple access, Time division multiple access, and Code division multiple access ·         Covers band pass modulation techniques such as Binary phase shift keying, Differential phase shift keying, Quadrature phase shift keying, Binary frequency shift keying, Minimum shift keying, and Gaussian minimum shift keying.
Mathematical model of the time varying wireless channel -- Detection theory, Estimation theory for the wireless communication -- Modulation techniques in wireless communication.
Keywords: Signal processing; Computer engineering; Computer networks .; Telecommunication; Signal, Speech and Image Processing; Computer Engineering and Networks; Communications Engineering, Networks